"I would say that might be all it is, is hope": The framing of herbicide resistance and how farmers explain their faith in herbicides. (January 2018) - Dentzman, Katherine
Highlights: Farmers explain their faith in herbicides through a techno-optimism master frame. This master frame closely aligns with an agricultural sociotechnical imaginary. Farmers frame the solution to HR weeds as continued development of new herbicides. Farmers frame the blame for HR weeds as an issue of mismanagement by farmers. Some farmers are challenging the frame and confronting an 'as-if' trust in herbicides.